PPDM INISIASI RUMAH KEMASAN DAN PEMASARAN PADA MITRA DI DESA RASAU JAYA SATU - Suwarni, Linda; Sarwono, Eko; Suryadi, Edy; selviana, Selviana (Vokasi Universitas Halu Oleo, 2019)
The potential of agriculture and home industries in Rasau Jaya Village is still not developing optimally. Lack of knowledge, awareness and skills regarding packaging and marketing of products is a problem faced by community groups engaged in agriculture and home industries. The partner village development program (PPDM) offers solutions to overcome the problems mentioned through: (a) Processing tofu into various flavored tofu chips, (b) Health checks, (c) Initiation of packaging and marketing houses, (d) Socialization of packaging and marketing house management, and (e) education on processing of complementary foods for breast milk and feeding provision of local food supplies (sweet corn). The method of implementation is carried out through outreach / counseling, mentoring and demonstration. The results of this service program are enhancing partners 'knowledge and skills in processing pong tofu into multi-flavored chips, initiating the development of packaging and marketing houses, understanding partner members' knowledge about early detection in non-communicable negotiations, and increasing understanding of how processed products work. Future assistance and assistance are needed from all parties, both the village government and regional health workers in fostering Mekar Sari and UKK Sekapur Sirih SMEs to realize creative and innovative SMEs and UKKs in supporting Rasau Jaya Village.